2018
DOI: 10.1111/aos.13942
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in arterial hypertension and ocular perfusion pressure definitions: Towards a consensus on blood pressure‐related parameters for glaucoma studies

Abstract: Purpose Glaucoma studies have long taken into account the blood pressure (BP) status of patients. This study summarizes and evaluates the impact of the different criteria that have been used for BP‐related variables in glaucoma research. Methods Studies included in two meta‐analyses that reviewed the role of BP in glaucoma were analyzed. Additional studies published after the search periods of the meta‐analyses were also included. Criteria for the definition of arterial hypertension and other BP‐related variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 82 publications
0
16
0
1
Order By: Relevance
“…study population, types of glaucoma, use of topical drugs). Moreover, various BP-and OPP-related parameters (e.g., MOPP, systolic OPP, diastolic OPP, MAP, SBP, DBP) were used, which rendered interpretation of the effect of OPP on glaucoma more complex, in line with the study by Barbosa-Breda et al 63 Therefore, to address the gap in consideration of heterogeneity between studies, we conducted systematic review and meta-analysis and confirmed that OAG patients had significantly lower MOPP than controls.…”
Section: Discussionmentioning
confidence: 88%
“…study population, types of glaucoma, use of topical drugs). Moreover, various BP-and OPP-related parameters (e.g., MOPP, systolic OPP, diastolic OPP, MAP, SBP, DBP) were used, which rendered interpretation of the effect of OPP on glaucoma more complex, in line with the study by Barbosa-Breda et al 63 Therefore, to address the gap in consideration of heterogeneity between studies, we conducted systematic review and meta-analysis and confirmed that OAG patients had significantly lower MOPP than controls.…”
Section: Discussionmentioning
confidence: 88%
“…Automated oscillometry (Infinity Delta; Dräger, Vienna, Austria) on the upper arm was used to measure systolic, diastolic, and mean arterial blood pressures (systolic blood pressure[SBP], diastolic blood pressure[DBP], and mean arterial pressure [MAP]) and pulse rate. As proposed previously, ocular perfusion pressure (OPP) in the sitting position was calculated as OPP = 2/3*MAP-IOP34 taking into account the pressure drop between the upper arm and the eye.…”
mentioning
confidence: 99%
“…It should be noted that we did not actually measure blood flow of retina using OCTA, but the imaging technique could be a useful tool to show the vascular changes by the index of VD. Hence our results of reduction in both RPC-and SVP-VD could be explained by decrease of MOPP according to the formula which leads to a drop in ocular perfusion and microvascular networks are of primary interest in glaucoma [19]. On the other hand, high-level evidence has shown that treatments decreasing IOP improve the retinal circulation and reduce the risk of development of glaucoma in OHT [27].…”
Section: Discussionmentioning
confidence: 53%